Preventing seizure occurrence following spontaneous intracerebral haemorrhage: A systematic review and meta-analysis of seizure prophylaxis. (April 2021) - Tran, Quincy K.; Bzhilyanskaya, Vera; Afridi, Leenah Z.; Ahmad, Mahmood; Palmer, Jamie; Rehan, Mehboob A.; Raffman, Alison; Rashid, Asma; Menne, Ashley; Pourmand, Ali
Highlights: Spontaneous intracerebral haemorrhage (ICH) is associated with high morbidity and mortality. Current data regarding the efficacy of seizure prophylaxis has been controversial. Our study found that seizure prophylaxis in adult patients with spontaneous ICH did not prevent seizure occurrence. Abstract: Introduction: Spontaneous intracerebral haemorrhage (ICH) is associated with high mortality and high morbidity, including seizures. Seizure prophylaxis is "not recommended" by the American Stroke Association, but practice variation still exists due to inconclusive data. We performed a meta-analysis to assess the current relevant literature to determine the efficacy of seizure prophylaxis following ICH. Methods: We performed searches of PubMed, Scopus, and Embase up to September 15, 2020. We included observational and randomized controlled studies reporting seizure prophylaxis and occurrence in adults with ICH. Outcomes were seizures, as defined by the authors, within 14 days of ICH and at the longest point of follow-up. We used random-effects models to estimate the odds ratios (ORs) for seizure prophylaxis and outcomes. The PROSPERO registration was CRD42019140493. Results: We included 8 studies (2852 patients) in our analysis. The mean (± standard deviation) age of the pooled patients was 65 (±4) years; 39 % (± 5%) were female. Seizure prophylaxis did not prevent seizures at the longest follow-up time (OR 0.708, 95 % CI 0.438–1.143, p = 0.158, I2 = 34 %). This result was confirmed in subgroup analyses using categorical variables and in meta-regressions using continuous variables. Additionally, seizure prophylaxis was not associated with preventing early seizures, defined as < 14 days of ICH (OR 0.66, 95 % CI 0.21–2.08, p = 0.48, I2 = 35 %). Conclusion: Seizure prophylaxis following ICH was not associated with seizure prevention in adults. Most included studies were observational. Further randomized controlled trials examining the efficacy of seizure prophylaxis in high-risk patients and different types of antiepileptic drugs are needed.